2005
DOI: 10.1007/s00542-004-0446-8
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of microneedle array using LIGA and hot embossing process

Abstract: We demonstrate a novel fabrication technology of the microneedle array applied to painless drug delivery and minimal invasive blood extraction. The fabrication technology consists of a vertical deep X-ray exposure and a successive inclined deep X-ray exposure with a deep X-ray mask whose pattern has a hollow triangular array. The vertical exposure makes triangular column array with a needle conduit. With the successive inclined exposure, the column array shapes into the microneedle array without deep X-ray mas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
53
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(53 citation statements)
references
References 9 publications
0
53
0
Order By: Relevance
“…Lithographic methods such as focused beam lithography, UV lithography, and X-ray lithography are relatively slow and expensive, and as a result these methods are suitable for prototyping and small volume production. In contrast, the hot embossing process Jaszewski et al 1998;Moon et al 2005;Chang and Yang 2005;Shan et al 2005;Chen et al 2005;Scheer et al 2004), which has demonstrated 10 nm resolution Scheer et al 2004), is becoming a dominant fabrication method for nano/microstructures when low cost and high throughput are desired.…”
Section: Introductionmentioning
confidence: 90%
“…Lithographic methods such as focused beam lithography, UV lithography, and X-ray lithography are relatively slow and expensive, and as a result these methods are suitable for prototyping and small volume production. In contrast, the hot embossing process Jaszewski et al 1998;Moon et al 2005;Chang and Yang 2005;Shan et al 2005;Chen et al 2005;Scheer et al 2004), which has demonstrated 10 nm resolution Scheer et al 2004), is becoming a dominant fabrication method for nano/microstructures when low cost and high throughput are desired.…”
Section: Introductionmentioning
confidence: 90%
“…In this area micro injection molding always is the one of the focus technologies for realizing micro parts for mass production out low cost (Michaeli et al 2000;Wintermantel et al 2008;Moon et al 2005;Turng and Kharbas 2003). However, as we know, micro injection molding is based on conventional injection molding process, so there are many defects and problems in this process as in the conventional process.…”
Section: Introductionmentioning
confidence: 96%
“…(Wicht and Bouchaud 2005;Wechsung et al 2002). As a result, micro injection molding appears as one of the most suitable processes for replicating microstructures with medium, even large production scales (Michaeli and Spennemann 2001;Moon et al 2005;Piotter et al 2001).…”
Section: Introductionmentioning
confidence: 99%